Eleven rings : the soul of success - Jackson, Phil (Penguin Press, 2013)
During his storied career as head coach of the Chicago Bulls and Los Angeles Lakers, Phil Jackson won more championships than any coach in the history of professional sports. Even more important, he succeeded in never wavering from coaching his way, from a place of deep values. Jackson was tagged as the "Zen master" half in jest by sportswriters, but the nickname speaks to an important truth: this is a coach who inspired, not goaded; who led by awakening and challenging the better angels of his players' nature, not their egos, fear, or greed. This is the story of a preacher's kid from North Dakota who grew up to be one of the most innovative leaders of our time. In his quest to reinvent himself, Jackson explored everything from humanistic psychology and Native American philosophy to Zen meditation. In the process, he developed a new approach to leadership based on freedom, authenticity, and selfless teamwork that turned the hypercompetitive world of professional sports on its head.--From publisher description.